Mechanical and structural characterization of CAD-CAM materials and enamel of deciduous and permanent teeth - Wada, Kanae; Garoushi, Sufyan; Wada, Junichiro; Iwamoto, Tsutomu; Vallittu, Pekka K; Lassila, Lippo (Japan, 2025)
In clinical applications, computer-aided design/computer-aided manufacturing (CAD-CAM) blocks must exhibit behavior similar to that of deciduous teeth. The purpose of this study was to evaluate the material properties and suitability of CAD-CAM as deciduous teeth. Experimental fiber-reinforced CAD-CAM composites (FRC) and various CAD-CAM (lithium disilicate ceramic: IPS, hybrid ceramic: VEM, five composite resins, and PMMA) and enamels (deciduous and permanent teeth) were subjected to nanoindentation to evaluate material properties, including nanohardness and nano-reduced elastic modulus. Energy dispersive X-ray spectrometry was conducted in combination with SEM to evaluate the elemental and microstructural properties. FRC-fiber (2.94 GPa), VEM-ceramic (3.20 GPa), and IPS (3.63 GPa) showed no statistically significant differences compared to deciduous enamel (3.37 GPa). Various CAD-CAM materials were confirmed to exhibit sufficient nanohardness and nano-reduced elastic modulus and a strong microstructure, indicating their potential for application in the restorative treatment of full crowns of deciduous teeth.